Tingkat kerentanan sosial pada kawasan kumuh di Kelurahan Rejomulyo, Kecamatan Semarang Timur - Farhan Afif; Nany Yuliastuti (Teknik PWK (Perencanaan Wilayah Kota), 2019)
Slum settlements in urban areas arise because of the inequality between supply and demand especially in the provision of housing. Rejomulyo Village is one of the areas that has  8.42 Ha of slum areas. Currently, there are 33% of the population has not graduated from school, 41% of the population is still working as an industrial worker and do odd jobs that relies on daily basic income. The characteristics of residents and slum areas in the Rejomulyo Village become a conducive tool in increasing social vulnerability. Therefore, this study aims to measure the level of social vulnerability of the slum residents in the Rejomulyo village. The research uses several variables namely economics, environmental health and shelter, gender, demographics and also access. The methods used in this research are descriptive analysis and scoring. The results of the study showed that the level of social vulnerability in Rejomulyo Village is in medium with residential health and environment as the most influential variable.